(untitled) (Annals of Medical Research, 2021)
Aim: Endometrial polyps are frequently associated with abnormal uterine bleeding. The kispeptin family is one of the peptides that play a role in reproductive functions and whose expression varies in various uterine pathologies. The aim of the study was to determine the relationship between serum Kisspeptin levels and endometrial polyps in women with premenopausal status.Material and Methods: The blood was collected prior to endometrial sampling from women admitted to the hospital due to abnormal uterine bleeding. According to the pathology results, patients were identified as polyp group (n=38) (endometrial polyps) and control group (n=50) (normal endometrial findings). Kisspeptin-54 levels were determined by ELISA method from serum obtained from venous blood. Results: There were no difference was found between the patients’ age, body mass index, gravida, para, abortus and the number of living children were compared (p>0.05). There was no statistically significant difference between the groups in terms of follicle stimulating hormone, luteinizing hormone and thyroid stimulating hormone values (p>0.05). Plasma kisspeptin (1.84±0.93 ng/dL and 1.32±0.47 ng/dL, p= 0.008) and estradiol (90.34±13.02 pg/mL and 81.75±12.36 pg/mL, p=0.002) levels were significantly higher in the polyp group than in the control group. After the Receiver Operating Characteristic (ROC) analysis the area under the curve (AUC) was 1.26 (p= 0.08), (95% CI, 0.550-0.782). The sensitivity value was 0.684 (0.512-0.819), the specificity was 0.620 (0.471-0.750).Conclusion: The serum Kisspeptin-54 and estradiol levels were found higher in patients with endometrial polyps.Keywords: Abnormal uterine bleeding; endometrial polyps; kisspeptin.